Escuela y televisión: Dos miradas reflexivas (2009)
This article presents a discussion about the media and schools. It presents an overview of using media in the educational realities recent emphasis on the respective television. The text makes a conceptual review of two paths problems that have approached the issue: a phone and an analytical look reflective. It is suggested, then, to a critical reading of the use of mass media on the part of the scholastic subjects.